Framing crisis response messages on Facebook: a second level agenda analysis of MH370 - Dayang Aizza Maisha, Abang Ahmad; Noratikah, Mohamad Ashari; Mus Chairil, Samani (EDP Sciences, 2017)
A crisis can certainly bring great threats to an organisation. In time of crisis, what the organisation says and does may impose significant effect on the organisation’s effort to survive its reputational damages. Although crisis responses are considered a common topic, this rapidly growing field of research is however vital to be critically explored. In light of Situational Crisis Communication Theory (SCCT) [1] and the Second-level Agenda Setting approach [2], this study seeks to analyse the message frames used by Malaysia Airlines System (MAS) in the formation of MH370 crisis response messages that that were disseminated directly to the organisation’s stakeholders on Facebook. The convergence of framing and second level agenda setting has made this study significant as it advances the explication of potential crisis communication effects by underscoring the distinct importance held by certain attributes and frames, in the content of a crisis response message. This paper also includes discussion on the directions for future research on crisis response strategies particularly in the local context.